Memahami Organisasi Kurikulum Pendidikan Agama Islam: Perspektif dan Evaluasi dalam Konteks Pendidikan Umum - Irawan, Hendri (Peradaban Journal of Interdisciplinary Educational Research, 2024)
The curriculum plays a vital role in the education system, determining the direction and effectiveness of the teaching and learning process. The Islamic Religious Education (PAI) curriculum in Indonesia has undergone frequent changes, facing challenges in terms of effectiveness and relevance to the needs of the times. This article explores the organization of the PAI curriculum, encompassing four types of organization: separate, correlated, unified, and integrated. The research method employed is qualitative, utilizing a literature review to evaluate the structure and implementation of the PAI curriculum. The evaluation reveals that although there has been progress in the integration of religious education in public schools, challenges such as balancing religious and general knowledge, as well as adapting to changing times, persist. This study concludes that there is a need for the development of a more effective and relevant PAI curriculum that aligns with the objectives of Islamic education. Kurikulum berperan penting dalam sistem pendidikan, menentukan arah dan efektivitas proses belajar-mengajar. Kurikulum Pendidikan Agama Islam (PAI) di Indonesia sering mengalami perubahan, menghadapi tantangan dalam efektivitas dan relevansinya dengan kebutuhan zaman. Artikel ini mengeksplorasi organisasi kurikulum PAI, mencakup empat jenis organisasi: terpisah-pisah, berkorelasi, satu kesatuan, dan terpadu. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan studi pustaka untuk mengevaluasi struktur dan implementasi kurikulum PAI. Evaluasi menunjukkan bahwa meskipun ada kemajuan dalam integrasi pendidikan agama di sekolah umum, tantangan seperti keseimbangan antara ilmu agama dan umum serta adaptasi terhadap perubahan zaman tetap ada. Penelitian ini menyimpulkan perlunya pengembangan kurikulum PAI yang lebih efektif dan relevan dengan tujuan pendidikan Islam.